Shifting and Sharing: Academic Physicians' Strategies for Navigating Underperformance and Failure. (November 2018) - LaDonna, Kori A.; Ginsburg, Shiphra; Watling, Christopher
Abstract : Purpose: Medical practice is uncertain and complex. Consequently, even outstanding performers will inevitably experience moments of underperformance and failure. Coping relies on insight and resilience. However, how physicians develop and use these skills to navigate struggle remains underexplored. A better understanding may reveal strategies to support both struggling learners and stressed practitioners. Method: In 2015, 28 academic physicians were interviewed about their experiences with underperformance or failure. Constructivist grounded theory informed data collection and analysis. Results: Participants' experiences with struggle ranged from patient errors and academic failures to frequent, smaller moments of interpersonal conflict and work–life imbalance. To buffer impact, participants sometimes shifted their focus to an aspect of their identity where they felt successful. Additionally, although participants perceived that insight develops by acknowledging and reflecting on error, they sometimes deflected blame for performance gaps. More often, participants seemed to accept personal responsibility while simultaneously sharing accountability for underperformance or failure with external forces. Paradoxically, participants perceived learners who used these strategies as lacking in insight. Conclusions: Participants demonstrated the protective and functional value of distributing responsibility for underperformance and failure. Shifting and sharing may be an element of reflection and resilience; recognizing external factors may provide a way to gain perspective and to preserve the self. However, this strategy challenges educators' assumptions that learners who deflect are avoiding personal responsibility. The authors' findings raise questions about what it means to be resilient, and how assumptions about learners' responses to failure may affect strategies to support underperforming learners.